Stereo visual odometry by combining points and lines - Gómez-Ojeda, Rubén; González-Jiménez, Antonio Javier (My University, 2018)
Most approaches to stereo visual odometry reconstruct the motion based on the tracking of point features along a sequence of images. However, in low-textured scenes it is often difficult to encounter a large set of point features, or it may happen that they are not well distributed over the image, so that the behavior of these algorithms deteriorates. This paper proposes a probabilistic approach to stereo visual odometry based on the combination of both point and line segment that works robustly in a wide variety of scenarios. The camera motion is recovered through non-linear minimization of the projection errors of both point and line segment features. The method, of course, is computationally more expensive that using only one type of feature, but still can run in real-time on a standard computer and provides interesting advantages, including a straightforward integration into any probabilistic framework commonly employed in mobile robotics.
Poster presented at ICVSS2016: international Computer Vision Summer School
Keywords: Robótica; Visual odometry; Stereo Vision; Feature points; Segments